Asymmetric Anion–π Catalysis on Perylenediimides. Issue 46 (14th October 2016) - Wang, Chao; Miros, François N.; Mareda, Jiri; Sakai, Naomi; Matile, Stefan
Abstract: Anion–π catalysis, that is the stabilization of anionic transition states on π‐acidic aromatic surfaces, has so far been developed with naphthalenediimides (NDIs). This report introduces perylenediimides (PDIs) to anion–π catalysis. The quadrupole moment of PDIs (+23.2 B) is found to exceed that of NDIs and reach new records with acceptors in the core (+70.9 B), and their larger surface provides space to better accommodate chemical transformations. Unlike NDIs, the activity of PDI catalysts for enolate and enamine addition is determined by the twist of their π surface rather than their reducibility. These results, further strengthened by nitrate inhibition and circular dichroism spectroscopy, support an understanding of anion–π interactions centered around quadrupole moments, i.e., electrostatic contributions, rather than redox potentials and charge transfer. The large PDI surfaces provide access to the highest enantioselectivities observed so far in anion–π catalysis (96 % ee ). Abstract : Space, finally ! The explicit investigation of perylenediimides for anion–π catalysis reveals a remarkably rich picture dominated by giant quadrupole moments, space to accommodate larger transformations, highest enantioselectivities so far, and decreasing activity with increasing twist.